Decision-making factors in holiday destination choice among Russian tourists - Zaytseva, Elena Vladimirovna, 1975- (2017)
Studies on travel destination choice have been a significant theme within tourism studies for years, but little is known about how Russian tourists make decisions about their holiday destinations. This study consisted of two parts. The first part attempted to identify most important push and pull motivational factors that Russian tourists report as affecting their holiday destination choice. The second part assessed leading constructs of behavioural intention when Russian tourists were choosing a holiday destination, with emphasizes on Iceland. The Theory of Planned Behavior (TPB) model was applied using its core constructs of behavioural intention. The study sample comprised 301 Russian tourists. In total, 20 push and pull motivational factors that could affect holiday destination choice were evaluated by ranking priorities and factor analyses; 44 variables were evaluated by factor analyses to identify the intention to visit Iceland on holiday. Results showed that the group of external pull motivators was stronger than the group of internal push motivations in Russian tourist holiday destination choice. Among the most significant external pull motivators were price and safety of destination. Subjective norms (reference groups’ opinion) have the greatest effect on respondents’ behavioural intentions to visit Iceland on vacation. Control beliefs and perceived behavioural control cannot be associated with real intentions to visit a destination in the study case. Giving specific attention to Russia, this study contributes to the expansion of the geographical and cultural range of tourism studies. The results would have practical use for tourism planning, and marketing and business opportunities. Þótt rannsóknir á því hvernig ferðamenn kjósa áfangastað hafi verið fyrirferðarmiklar í ferðamálafræðum um árabil er enn lítið vitað um það hvernig ákvarðanatöku rússneskra ferðamanna er háttað. Þessi rannsókn sem hér er greint frá var tvískipt. Í fyrri hlutanum var reynt að gera grein fyrir veigamestu ýti- og ...